Intonational production as a window into children’s early pragmatic competence: The case of the Norwegian polarity focus and two jo particles - Helganger, Line Sjøtun; Falkum, Ingrid Lossius (Frontiers in Psychology, 2023)
The use of the Norwegian intonation pattern Polarity Focus highlights the polarity of a contextually given thought and enables the speaker to signal whether she believes it to be a true or false description of some state of affairs. In this study, we investigate whether preschool children can produce this intonation pattern and what their productions reveal about the development of their early pragmatic abilities. We also explore their use of Polarity Focus in combination with two particles encoded by the linguistic form jo: a sentence-initial response particle, and a sentence-internal pragmatic particle. We used a semi-structured elicitation task consisting of four test conditions of increasing complexity to shed light on the developmental trajectory of the mastery of Polarity Focus. Our results show that already from the age of 2 children are proficient users of this intonation pattern, which occurs in three out of four conditions for this age group. As expected, only 4- and 5-year-olds produced Polarity Focus in the most complex test condition that required the attribution of a false belief. We further found production of sentence-initial response particle jo by all age groups, both in combination with Polarity Focus and alone. Production of the sentence-internal pragmatic particle jo, felicitously co-occurring with Polarity Focus, emerges around age 3. This study presents the first experimental evidence of Norwegian children’s mastery of intonation as a communicative device in language production and their use of the two jo particles. We show how intonational production can be used as a window into children’s early pragmatic competence: The mastery of the production of Polarity Focus can be seen as an early linguistic manifestation of the cognitive abilities for the attribution of thoughts and epistemic vigilance towards propositional content.